THE EMERGENCE OF CHATGPT: EXPLORING ITS POTENTIAL IN DESIGNING ISLAMIC RELIGIOUS EDUCATION LEARNING - Suhendi, Saca; Yulianti, Ferina; Isnaini, Nurul Azizatul; Jamal, Jamal; Tamim, Ahmad; Wulandari, Reksahati; Ruswandi, Uus (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
The phenomenon of the emergence of ChatGPT certainly provides a new colour in various sectors of life, including in the field of education, both general education and Islamic education. ChatGPT is reliable enough to have potential in the learning process, but in its application, it can cause pros and cons. Therefore, this study aims to describe the potential of ChatGPT in Islamic Religious Education and the challenges faced in applying ChatGPT in Islamic Religious Education. This type of research is qualitative research with a library research method. The results showed that ChatGPT has great potential to have a significant impact on Islamic Religious Education learning because it can increase the productivity of both teachers in facilitating the development of teaching tools and materials and students in exploring ideas freely. However, in its application, ChatGPT has several challenges that can cause problems related to accuracy, ethics, and compatibility with values in Islamic education, as well as general academic integrity issues that include the risk of plagiarism, fraud, and misuse of information sources. ChatGPT has enormous potential in facilitating the learning process of Islamic Religious Education, but behind this potential, there are several challenges faced in its application. Therefore, teachers must always be proactive in integrating ChatGPT into the learning process to ensure that the information obtained by Islamic values is upheld. Teachers' policies in using ChatGPT for students also need to be carried out so that the degradation of critical reasoning and in-depth understanding of Islamic Religious Education materials does not occur.